Smith‐Magenis syndrome: Clinical and behavioral characteristics in a large retrospective cohort. Issue 4 (5th January 2021) - Rive Le Gouard, Nicolas; Jacquinet, Adeline; Ruaud, Lyse; Deleersnyder, Hélène; Ageorges, Faustine; Gallard, Jennifer; Lacombe, Didier; Odent, Sylvie; Mikaty, Myriam; Manouvrier‐Hanu, Sylvie; Ghoumid, Jamal; Geneviève, David; et al.
Abstract: Smith‐Magenis syndrome (SMS), characterized by dysmorphic features, neurodevelopmental disorder, and sleep disturbance, is due to an interstitial deletion of chromosome 17p11.2 (90%) or to point mutations in the RAI1 gene. In this retrospective cohort, we studied the clinical, cognitive, and behavioral profile of 47 European patients with SMS caused by a 17p11.2 deletion. We update the clinical and neurobehavioral profile of SMS. Intrauterine growth was normal in most patients. Prenatal anomalies were reported in 15%. 60% of our patients older than 10 years were overweight. Prevalence of heart defects (6.5% tetralogy of Fallot, 6.5% pulmonary stenosis), ophthalmological problems (89%), scoliosis (43%), or deafness (32%) were consistent with previous reports. Epilepsy was uncommon (2%). We identified a high prevalence of obstipation (45%). All patients had learning difficulties and developmental delay, but ID range was wide and 10% of patients had IQ in the normal range. Behavioral problems included temper tantrums and other difficult behaviors (84%) and night‐time awakenings (86%). Optimal care of SMS children is multidisciplinary and requires important parental involvement. In our series, half of patients were able to follow adapted schooling, but 70% of parents had to adapt their working time, illustrating the medical, social, educative, and familial impact of having a child with SMS. Abstract : Smith‐Magenis Syndrome (SMS) is a rare disease due to either a small loss in the chromosome 17 or a mutation in a specific gene at the same location. This neurodevelopmental disorder is characterized by learning and intellectual disabilities, behavioral disorder and a specific sleep disturbance with an inversion of the day‐night cycle. Here, we report an important number of SMS patients and thus provide a better support for patients and families.